Validation of a pandemic-proof, decentralized cardiovascular trial: scalable design produces rapid recruitment, high engagement and protocol adherence in DeTAP (Decentralized Trial in Afib Patients). (14th October 2021) - Josan, K; Touros, A; Petlura, C; Parameswaran, V; Grewal, U; Senior, M; Viethen, T; Mundl, H; Seninger, C; Luithle, J; Mahaffey, K; Turakhia, M; et al.
Abstract: Background: The COVID-19 pandemic has curtailed clinical trial activity significantly. Decentralized clinical trial (DCT) designs may lower cost, expand trial access, and reduce exposure risk for patients and staff. Whether such designs can be used for large, pivotal drug trials is not known. Purpose: We performed a feasibility study to inform whether a large phase 3 Cardiovascular DCT can achieve high quality trial results and also withstand health crises such as the COVID-19 pandemic. The DeTAP (Decentralized Trial in Afib Patients) was a single-arm, observational study that integrated a suite of digital health technologies, including paired home sensor devices, into a 100% virtual trial experience for atrial fibrillation (AF) patients on anticoagulation. Methods: We recruited 100 AF patients over age 55 on oral anticoagulation (OAC) by traditional methods or by social media ads placed California-wide. Subjects completed an online prescreening, uploaded their active OAC prescription, and completed an e-consent via SMS message link. Participants downloaded a customized study app to integrate surveys and data from study-supplied wireless blood pressure (BP) and 6 lead EKG sensors (Figure 1A). Participants completed pre- and post-study engagement surveys, weekly OAC adherence surveys, 4 study televisits, 4 ECG/BP readings, and 4 post-study surveys over a 6 month period. The primary endpoints were protocol engagement-based measurements that quantified percent completion of: 1) televisits 2) surveys, 3) ECG/BP readings requirements. Secondary endpoints were the % changes in: 1) OAC adherence (OACA), 2) nuisance bleeding (NB), 3) individual patient engagement surveys. Results: 100 participants were recruited in 26 days (traditional: 6 in 2 weeks; social media: 94 in 12 days) with a dramatic surge in enrollment driven by social media ads (Figure 1B, Table). A recruitment overflow occurred with >200 eligible candidates on a waitlist. All key study completion metrics showed high compliance: televisit (91%); surveys (85%); ECG/BP completion (90%). Overall OACA was unchanged, but for subjects who reported low initial OACA, there was significant improvement at 6 months (85±16% to 98±6%; p=0.002). 47 participants (57%) reported NB, which did not correlate with OACA. Participant engagement measure scores (PAM-13) trended higher (baseline, 70%; 6 months, 74%, p=0.32). Lastly, study participants exhibited strong interest in participating in a larger experimental drug DCT study (90%) in the future. Conclusion: The DeTAP study, conducted fully during the COVID-19 pandemic, demonstrates that a decentralized CV medical intervention trial is feasible and can achieve rapid recruitment, high study retention, physiologic and adverse event reporting, and high study engagement via the proper integration of digital technologies and a dedicated DCT study coordination effort. These findings could be informative for virtualizing large pivotal clinical trials at scale. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer AG